Organizational Management Policies and Practices - Machado, Carolina; Davim, Joao Paulo (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Organizations are increasingly facing continuous and highly complex changes that require more proactive strategies, policies and management practices. Conscious of this reality, this book provides information and debate on principles, strategies, models, techniques, methodologies and applications of organizational management in the field of industry, commerce and services. Organizational Management communicates the latest developments and thinking on the organizational management subject world-wide, and seeks cultural and geographic diversity in studies and uses of organizational management that have a special impact on organizational communications, change processes and work practices. With an emphasis on the way organizations define and develop their management policies and practices in order to acquire more competitive advantages in the global market, this book is crucial to any practitioner or researcher of current organizational management.